Analisis Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Value Consult Jakarta Selatan - Syahindah Purnama Gusnia; Muhammad Yuda Alhabsyi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze in depth the influence of motivation and work environment on employee performance at PT. Value Consult, South Jakarta. The focus of the study is directed at the extent to which work motivation and work environment conditions can contribute to increasing employee productivity and performance effectiveness. This study uses a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of a number of key informants. The results show that motivation formed through a fair reward system, providing opportunities for self-development, and managerial support has a significant influence on increasing employee morale and responsibility. In addition, a comfortable work environment, harmonious work relationships, and adequate work facilities contribute to creating a positive work atmosphere that supports the improvement of individual and team performance. Thus, the synergy between the right motivation and a conducive work environment is a strategic factor in improving employee performance and achieving organizational goals in a sustainable manner.